Perspective of women health care workers of a medical institute on care of their under-five child during COVID-19 pandemic - Sood, Vibhusha; T., Mahalakshmy; Krishna, Anagha U.; L., Subitha; Mondal, Nivedita (International Journal Of Community Medicine And Public Health, 2026)
Background: The COVID-19 pandemic significantly increased the burden on healthcare practitioners (HCPs), particularly women with young children, affecting their ability to balance professional responsibilities and childcare. Evidence on coping strategies among women HCPs with under-five children in the Indian context remains limited. Methods: A qualitative study using a Heideggerian hermeneutic phenomenological approach was conducted in a tertiary care teaching hospital in South India. Twenty women HCPs with children under five years were recruited using purposive and snowball sampling. Data were collected through in-depth telephonic interviews and analyzed using a combination of inductive and theoretical thematic analysis. Results: Two overarching themes emerged: Challenges in providing nurturing care and enabling environment for caregiving. Participants reported difficulties in accessing healthcare services, maintaining breastfeeding, ensuring adequate nutrition, supporting early childhood development, and providing responsive caregiving. Structural challenges included closure of childcare services, lack of domestic support, long working hours, and limited workplace flexibility. Psychological stress, emotional trauma, and spillover effects on family life were prominent. Coping strategies included problem-focused approaches such as seeking social support, adhering to infection control practices, and creating home-based learning environments, as well as emotion-focused strategies like positive reappraisal and emotional support. Conclusions: Women HCPs faced multifaceted challenges in balancing childcare and professional duties during the pandemic. Strengthening workplace policies, childcare support, and mental health interventions is essential to support their well-being and sustain healthcare delivery during crises.